2006
DOI: 10.1021/jf053017f
|View full text |Cite
|
Sign up to set email alerts
|

Carnobacterium Species:  Effect of Metabolic Activity and Interaction with Brochothrix thermosphacta on Sensory Characteristics of Modified Atmosphere Packed Shrimp

Abstract: The importance of carnobacteria as spoilage microorganisms or potential protective cultures in food is not resolved, and little is known about their metabolism during growth in specific products. This study used chromatographic techniques including GC-MS and HPLC to evaluate the spoilage metabolism of Carnobacterium divergens, Carnobacterium maltaromaticum, and Carnobacterium mobile. Metabolic activity was studied in cooked and peeled modified atmosphere packed (MAP) shrimp at 5 degrees C as carnobacteria has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
106
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(128 citation statements)
references
References 32 publications
15
106
1
2
Order By: Relevance
“…Its presence is related to a creamy dairy odor (40,41), and Dainty et al (9) have reported that the accumulation of acetoin was not unpleasant and caused the meat to be regarded not as spoiled but rather as "not fresh." Another important odoractive volatile compound detected in this study was 1-octen-3-ol, a common oxidized product from lipids, which was also found in meat and shrimp inoculated with strains of C. maltaromaticum and C. divergens (12,26). Butanoic acid was the main carboxylic acid produced in all the samples analyzed.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Its presence is related to a creamy dairy odor (40,41), and Dainty et al (9) have reported that the accumulation of acetoin was not unpleasant and caused the meat to be regarded not as spoiled but rather as "not fresh." Another important odoractive volatile compound detected in this study was 1-octen-3-ol, a common oxidized product from lipids, which was also found in meat and shrimp inoculated with strains of C. maltaromaticum and C. divergens (12,26). Butanoic acid was the main carboxylic acid produced in all the samples analyzed.…”
Section: Discussionsupporting
confidence: 51%
“…3-Methyl-1-butanol and 2-ethyl-1-hexanol were the most frequently detected alcohols after 1-octen-3-ol. High concentrations of 3-methyl-1-butanol were found in shrimp inoculated with C. maltaromaticum (26). Several aldehydes and alcohols known to derive from lipid oxidation in meat are absent from (14,40).…”
Section: Discussionmentioning
confidence: 97%
“…Currently, the focus is mainly on the systematic study of wellknown spoilage-related species (13)(14)(15)(16)(17)(18) in various food matrices and the development of methods to suppress their growth and offensive metabolism through the application of innovative technologies. The spoilage-related populations can be studied as a consortium with the help of culture-independent approaches in order to look at changes to the composition of the microbial communities in response to environmental factors related to food storage, such as temperature and packaging technology (19,20), as well as technological parameters (21).…”
mentioning
confidence: 99%
“…C. divergen merupakan bakteri pembusuk yang menghasilkan off odor yang lemah dideskripsikan sebagai bau susu mendidih, bau fermentasi maupun bau keju basi. Laursen et al (2006) menjelaskan bahwa C. maltaromaticum menghasilkan bau tidak sedap yang paling kuat yaitu bau klorin dan bau asam yang menyebabkan reaksi mual, diduga disebabkan karena produksi amoniak, berbagai macam alkohol, aldehid, dan keton. Menurut Jaffres et al (2011), C. maltaromaticum pada udang menghasilkan senyawa 3-metil-1-butanal, 2-metil-1-butanal, 2-metil-1-butanol, etil asetat, 2-metil-1-propanal, 2,3-butanedione, asetaldehid, 3-metil-2-butanon, 3-metil-1-butena, tiokarbamid dan siklopentanol.…”
Section: Nilai Organoleptik Rasaunclassified